Suppressive effects of adenosine on the 5-lipoxygenase pathway in human polymorphonuclear leukocytes - Flamand, Nicolas; Plante, Hendrick; Picard, Serge; Austin, Michelle; Surette, Marc E.; Krump, Éric; Bourgoin, Sylvain; Borgeat, Pierre (Drug development research, 2001)
Leukotrienes are potent mediators of inflammation and host defense. They are also involved in inflammatory and allergic diseases. While numerous studies have investigated the stimulatory mechanisms of leukotriene biosynthesis in phagocytes by inflammatory agents (chemoattractants, cytokines, etc.), the mechanisms responsible for the physiological downregulation of leukotriene biosynthesis have been the subject of very few investigations so far. It has, however, been reported that E‐type prostaglandins are potent inhibitors of leukotriene biosynthesis in chemoattractant‐stimulated neutrophils and we have recently shown with in vitro studies that endogenous adenosine is a potent inhibitor of leukotriene biosynthesis by neutrophils. The present review summarizes our studies demonstrating that adenosine downregulates leukotriene biosynthesis via an interaction with the adenosine A2a receptor on neutrophils; studies aimed at defining the mechanisms of action of adenosine in this process have demonstrated that adenosine inhibits the translocation of the cytosolic enzyme 5‐lipoxygenase to nuclear structures, a process required for leukotriene biosynthesis in neutrophils. Our studies also demonstrated that exposure of human neutrophils to the adenosine A2a receptor agonist CGS‐21680 result in a profound inhibition of the release of arachidonic acid upon cell stimulation. While the previously reported inhibitory effect of adenosine on calcium influx elicited in ligand‐activated neutrophils does not appear to be involved in the inhibitory effects of adenosine on leukotriene biosynthesis, strong evidence supports the implication of elevation of intracellular cyclic AMP concentration both in the inhibition of 5‐lipoxygenase translocation and arachidonic acid release. Drug Dev. Res. 52:397–405, 2001. © 2001 Wiley‐Liss, Inc.